Evaluation of the impact of tricuspid regurgitation on the right ventricle and atrium of the heart caused by pacemaker leads - du Toit, N.; Botes, L.; Basson, W.; Thomas, V. (SA Heart Journal, 2024)
Introduction: The number of permanent device implantations to treat conduction disorders has dramatically increased over the past decade. The aim of the study was to investigate the development of lead-induced tricuspid regurgitation (TR) after permanent endocardial lead implantation. Methods: This prospective analytical observational study included 30 adult patients (≥18 years) that qualified for a cardiac pacemaker. Before implantation, demographic and anthropometric data were recorded. A 2D echocardiogram was performed to evaluate TR prior to implantation and at 6-week and 9 - 16-month followups. TAPSE and tissue doppler imaging (RV S’) were used to evaluate right ventricular function and basal and mid-right ventricular (RV) diameter and right atrial (RA) area. Results: The TR grade significantly worsened in 46% of patients from baseline to the 9 - 16-month postimplantation. However, the TR was not clinically significant. RV function, RV dimension and RA area remained within normal reference ranges. There was a negligible correlation between TR at baseline vs. the 9 - 16-month follow-up for TAPSE, RA area, basal and mid-RV diameter. Conclusion: After long-term follow-up, TR grade worsened after lead implantation, but not to clinically significant (moderate or severe) levels.